Agile logic for SaaS implementation : Capitalizing on marketing automation software in a start-up - Mero, Joel; Leinonen, Miira; Makkonen, Hannu; Karjaluoto, Heikki (Elsevier, 2022)
The emergence of Software-as-a-Service (SaaS) has facilitated agile technology implementation that focuses on iterative adaptations via learning by doing rather than the realization of a predesigned implementation plan. This study conceptualizes such an agile approach and explicates its operationalization via a four-year qualitative case study of a business-to-business (B2B) start-up firm’s implementation of a HubSpot marketing automation (MA) SaaS. The study shows how agile implementation continuously introduces adaptations to SaaS features and organizational routines for improving their mutual fit given the organization’s goals. The study also contributes to theory by offering a novel framework for managing agile implementation processes. The findings identify the key processes of sales lead management, content marketing, and customer intelligence through which start-up firms may capitalize on MA software.
Keywords: Agile methodologies; Cloud computing; Marketing automation; Technology adoption; SME; Software-as-a-service; fi=Markkinointi|en=Marketing|